2015
DOI: 10.15184/aqy.2014.9
|View full text |Cite
|
Sign up to set email alerts
|

Archaeological evidence for ancient Maya water management: the case of Nakum, Petén, Guatemala

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Evidence for drought is only relevant for understanding collapse if it can be demonstrated that limited water supplies would have posed major problems for ancient Maya polities. A growing body of archaeological and geoarchaeological research (e.g Lentz et al, 2014;Lucero, 2002;Luzzadder-Beach et al, 2012;Scarborough et al, 2012;Źrałka and Koszkul, 2015). has explored this topic, highlighting the importance of ancient Maya water conservation and water infrastructure for Classic Period agriculture and politics.…”
mentioning
confidence: 99%
“…Evidence for drought is only relevant for understanding collapse if it can be demonstrated that limited water supplies would have posed major problems for ancient Maya polities. A growing body of archaeological and geoarchaeological research (e.g Lentz et al, 2014;Lucero, 2002;Luzzadder-Beach et al, 2012;Scarborough et al, 2012;Źrałka and Koszkul, 2015). has explored this topic, highlighting the importance of ancient Maya water conservation and water infrastructure for Classic Period agriculture and politics.…”
mentioning
confidence: 99%
“…The LiDAR survey in the MCKB system has provided new insights into the control of water. The MCKB has no perennial rivers or lakes, aside from mature marshes on a small scale ( civales ), requiring the ancient Maya to construct large reservoir systems for water collection and rainwater management (see Chase and Cesaretti 2018 for similar observations in Caracol and Tikal, as well as Nakum; Źrałka and Koszkul 2015). LiDAR data located 195 artificial water reservoirs (termed aguadas by locals, although naturally occurring aguadas are rarely found in the basin) and a series of monumental reservoir systems designed for large water capture and control in the southern half of the MCKB.…”
Section: Monumentality Of Ritual and Religious Architecture Ballcourt...mentioning
confidence: 99%
“…The first is the rim of a cylindrical vessel found in the core of Structure 14 that borders Patio 1 on the southeast (Figure 3a, Table 1). This structure played a prominent role in the religious and social life of Nakum, serving as one of the major temples, which for at least some part of its existence served as a provisional burial place where esteemed individuals might have been located before the final burial took place (Źrałka and Koszkul 2015). Many beautiful vessels, including the examples described in this paper, were deposited in its core in what must have been ceremonial activity related to the rebuilding and expansion of this construction.…”
Section: Middle Classic and Connections With Naranjomentioning
confidence: 99%